Self Efficacy dalam Pembelajaran Online Matematika - Fransisca Tanjung Dian (J-PiMat : Jurnal Pendidikan Matematika, 2022)
Abstract. The ability of self-efficacy is considered to be closely related to students' mathematical learning outcomes, especially in how far students have confidence and want to continue trying to solve mathematical problem solving problems. In face-to-face learning, the four main sources of creating self-efficacy abilities are mastery experiences, modeling, social persuasion, and physiological states (Bandura, 1997). However, along with technological developments and the demands of the situation in the midst of a pandemic, teachers and students must have a strategy to continue to develop self-efficacy abilities, even though learning at this time can only be done through distance or online learning. The purpose of this article is to present several alternative ways to continue to develop students' self-efficacy abilities in the context of an online learning environment, especially in the field of mathematics. The writing of this article uses the method of literature review from books and articles. There are three subtopics that will be explained, namely what self-efficacy abilities are, how students' self-efficacy abilities can be formed, and how to develop self-efficacy abilities in online mathematics learning.